Combination of PSA density and MLR improves the diagnostic accuracy of prostate cancer - Guo, Feng; Maolake, Aerken; Ni, Zecheng; Li, Xun; Liu, Bide; Tang, Zetian; Shi, Zhenfeng; Li, Jiuzhi (Frontiers in Oncology, 2025)
Prostate-specific antigen (PSA) is used to screen for prostate cancer for decades. However, PSA has poor specificity in prostate cancer screening within the 4.0- to 10.0-ng/mL range. This study aimed to develop a new prediction model for PCa in patients with a PSA level of 2.5–20 ng/mL. The clinical data of 80 patients with PSA 4–22 ng/mL from 2016 to 2022 were selected for retrospective analysis. Prostate volume was estimated by suprapubic ultrasonography. PSA and the inflammatory markers like neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) in peripheral blood were analyyzed to assess their value in PCa. The diagnostic performance of PSA, PSA density (PSAD), and inflammatory markers, respectively, was estimated by ROC curve. The areas under the ROC curve for f/t PSA, PV, PSAD, MLR, NLR, and PLR for predicting PCa in patients with a PSA level of 4.0–22.0 ng/mL were 0.7375, 0.7774, 0.8294, 0.5945, 0.5571, and 0.5437, respectively. The PSAD performed better than f/t PSA and PV in the diagnosis of PCa. The specificity of PSAD was higher than that of f/tPSA when tPSA was in the gray zone (between 4 and 10 ng/mL). The area under the curve (AUC) increased when PSAD was combined with MLR in patients with PSA 4–10 ng/mL and patients with PSA 10–22 ng/mL, and the positive predictive values were 81.81% and 90.91%, respectively (P = 0.0008 and P = 0.0002). PSAD has a moderate diagnostic value for PCa detection. The combination of PSAD and MLR could improve the diagnostic accuracy in PCa diagnosis.